2018
DOI: 10.1021/acs.iecr.8b03092
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of HCl on Calcined Ca and Zn Hydrotalcite-like Compounds (HTLs) at Medium-High Temperature in Flue Gas

Abstract: The high level of HCl generated from municipal solid-waste incinerators at 350–650 °C is considered a primary chlorine source for emitted toxic polychlorinated dibenzodioxins and polychlorinated dibenzofurans. Herein, calcium (Ca) and zinc (Zn) hydrotalcite-like compounds (HTLs) were prepared to remove HCl at different reaction temperatures and initial HCl concentrations. The mechanism of the adsorption of HCl by the HTLs and calcined HTLs (HTOs) was investigated using thermogravimetric analysis, X-ray powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…16 Many adsorbents with superior performances for adsorbing HCl have been developed, including mineral materials, 17 porous carbon materials, 18 and hydrotalcite-like compounds. 19 However, their dechlorination efficiencies decrease significantly as the temperature rises, so they fail to be applied in HTR. The related studies reported that CaO has an extremely strong adsorption potential for acidic gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Many adsorbents with superior performances for adsorbing HCl have been developed, including mineral materials, 17 porous carbon materials, 18 and hydrotalcite-like compounds. 19 However, their dechlorination efficiencies decrease significantly as the temperature rises, so they fail to be applied in HTR. The related studies reported that CaO has an extremely strong adsorption potential for acidic gases.…”
Section: Introductionmentioning
confidence: 99%
“…The solid acid removal is an advanced technology, but it faces the challenge that though the species of HCl, Cl and Cl 2 are tiny, they are strongly oxidative to Hg 0 (g) . Many adsorbents with superior performances for adsorbing HCl have been developed, including mineral materials, porous carbon materials, and hydrotalcite-like compounds . However, their dechlorination efficiencies decrease significantly as the temperature rises, so they fail to be applied in HTR.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, at 250 to 450 °C, the high concentration of HCl can enhance the toxicity of PCDD/Fs (Li et al 2015a ; Lundin et al 2013 ). Many such sorbent materials exhibit unsatisfactory adsorption capacity, especially at high temperatures with the HCl adsorption capacities of these materials decreasing drastically as temperature rises (Cao et al 2018a ; Chibante et al 2010 ; Shemwell et al 2001 ). Consequently, recent research has focused on developing efficient sorbents with high adsorption capacity at medium-high temperatures, especially those exceeding 450 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Although incineration is a superior energy generation waste disposal method for conserving land area, serious gas pollution and generation of solid wastes always accompany such processes. Amongst these pollutants, hydrogen chloride (HCl), a harmful gas, can do much harm not only to the human body [5][6][7][8], but also via the corrosion of the incinerator and pipes [9,10]. It has been reported that at medium-high temperature (250-450 • C), HCl can be efficiently converted into polychlorinated dibenzodioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The layered double oxides (LDOs), which possess higher specific surface areas and more active sites, can be obtained by calcining the LDHs [31]. In our previous reports, some LDOs, such as Ca-Mg-Al, Ca-Zn, and Mg-Fe LDOs [5,32,33], were found to have high HCl adsorption capacity, and efficient removal capacity due to the newly-formed metal oxides during the pretreatment [6,7].…”
Section: Introductionmentioning
confidence: 99%